International Effects of Tax Reforms. (IMF Working Papers; Working Paper ;, 1988)
This paper highlights the significance of open-economy considerations in the analysis of tax reforms. It focuses on domestic and international consequences of revenue-neutral conversion between income and value-added tax systems. The principal result is that the direction of changes in key macroeconomic variables consequent on such tax conversions depends critically on the current account position. For example, a conversion from an income to a value-added tax system lowers the world interest rate if the country adopting the reform runs a surplus in the current account of its balance of payments, and vice versa.